THE APPLICATION OF á¸¤ABL MIN ALLÄ€H AND á¸¤ABL MIN AL-NÄ€S ELEMENTS IN ISLAMIC CODE OF ETHICS: AN EXPLORATORY CASE STUDY - Kamri, Nor ’Azzah; Ramlan, Siti Fairuz (International Journal of Economics, Management and Accounting, 2015)
Work is often perceived as a means to pursue material interest and basic human needs. Hence, the notion of work has become a meaningless routine that engage man with a series of tasks and duties, which, subconsciously, has made man void of spiritual fulfillment. To address this, Islam ruled on the elements of human to God relationship (á¸¥abl min AllÄh) and the fellow human relationship (á¸¥abl min al-nÄs) as the foundation of work ethic that seeks to fulfill both physical and spiritual concerns. Embarking on this idea, this article seeks to explore the application of both elements in cultivating ethical conduct in the workplace by addressing the question of whether the principles are given proper emphasis in employeesâ€™ ethical work conduct. This research employed two modes of data collection â€“ survey and interview. The survey is conducted on 166 employees of Tabung Haji (Pilgrims Fund Board), examining to what extent these elements are applied in their work; interview with the manager of Tabung Haji was also conducted to understand the managementâ€™s commitment in implementing the organizational code of ethics, known as the Work Values and Ethics of Tabung Haji (NEKTH). The outcome from interviews and survey has shown that both elements were given proper emphasis. The survey indicates that one of the principles, the relationship with Allah (á¸¥abl min AllÄh), is more emphasized than the human relationship, which was assumed to be the driving force of the employeesâ€™ ethical practices. The study proves that the inculcation of the principles is significant in reducing work misconduct as well as in promoting ethical work culture. This article aims at providing a deeper insight into the framework of the Islamic code of ethics, and subsequently raising awareness among managers on the significance of the elements in cultivating ethical practices at the workplace.